2002
DOI: 10.1093/emboj/cdf311
|View full text |Cite
|
Sign up to set email alerts
|

R-loop-dependent rolling-circle replication and a new model for DNA concatemer resolution by mitochondrial plasmid mp1

Abstract: The mitochondrial (mt) plasmid mp1 of Chenopodium album replicates by a rolling-circle (RC) mechanism initiated at two double-stranded replication origins (dso1 and dso2). Two-dimensional gel electrophoresis and electron microscopy of early mp1 replication intermediates revealed novel spots. Ribonucleotide (R)-loops were identi®ed at dso1, which function as a precursor for the RCs in vivo and in vitro. Bacteriophage T4-like networks of highly branched mp1 concatemers with up to 20 monomer units were mapped and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In support of this, Flores and Lambert provided evidence that HPV16 and HPV31 undergo a shift in the mode of replication upon differentiation (69). In undifferentiated cells, HPV replicates bidirectionally; however, two-dimensional (2D) gel analysis revealed that productively replicating genomes exhibit branched structures, including X structures and simple Y arcs, consistent with strand invasion (Holliday junction formation) and unidirectional (rolling-circle) replication, respectively (70,71). These studies offer support for our findings that recombination is important for successful viral genome amplification and suggest that productive replication may occur through rolling-circle replication and concatemer formation.…”
Section: Discussionsupporting
confidence: 73%
“…In support of this, Flores and Lambert provided evidence that HPV16 and HPV31 undergo a shift in the mode of replication upon differentiation (69). In undifferentiated cells, HPV replicates bidirectionally; however, two-dimensional (2D) gel analysis revealed that productively replicating genomes exhibit branched structures, including X structures and simple Y arcs, consistent with strand invasion (Holliday junction formation) and unidirectional (rolling-circle) replication, respectively (70,71). These studies offer support for our findings that recombination is important for successful viral genome amplification and suggest that productive replication may occur through rolling-circle replication and concatemer formation.…”
Section: Discussionsupporting
confidence: 73%
“…The recombination-based mtDNA replication model has recently gained strong support from studies suggesting that the replicative forks in Candida albicans mtDNA are generated from recombination intermediates (196). The presence of recombination-based replication in human heart and brain (87) and in plant mitochondria (197)(198)(199) has also been proposed. The physiological impact of this specific mechanism vis-à-vis the conventional RNA-primed replication mode is yet to be substantiated.…”
Section: Linking Mtdna Recombination Repair and Replicationmentioning
confidence: 99%
“…The DNA in the gel was transferred to a Hybond-N ϩ membrane (Amersham Biosciences, Piscataway, NJ) in 10ϫ SSC (1.5 M NaCl, 0.15M sodium citrate) by capillary blotting and was analyzed by a Southern hybridization with 32 Plabeled pUC119 DNA, which shares some sequence with pMK2 DNA and thus can be used as a specific probe. The DNA species on the two-dimensional gel were assigned as described previously (Backert, 2002).…”
Section: Analyses Of Mt-pmk2 Dna Isolated From Cells By Standard One mentioning
confidence: 99%
“…The mt-pMK2 DNA was detected by Southern hybridization by using the [ 32 P]pMK2 DNA-probe, after separation by size in the first dimensional electrophoresis and by shape in the second dimensional run. (C) Schematic diagram; 1, linear monomer; m (area), nicked circular monomer; 2, circular multimers; c (area), linear concatemers (see Backert, 2002 for the assignments of DNA species); 1D, the first dimensional run; 2D, the second dimensional run. (D) The twodimensional gel profile of the mt-pMK2 DNA isolated from MHR1 cells grown at 34°C.…”
Section: The Effects Of Mhr1p Overproduction On the Vegetative Segregmentioning
confidence: 99%